To study the anatomic and intraoperative factors responsible for gas bubble migration in the anterior chamber during femtosecond laser-assisted in situ keratomileusis (FS-LASIK) flap creation - Suman Lata; Sohini Mandal; Rajesh Sinha; Jeewan S. Titiyal (Indian Journal of Ophthalmology)
Purpose: This study investigates the factors responsible for gas bubble migration into the anterior chamber during femtosecond-assisted laser-assisted in situ keratomileusis (FS-LASIK) flap creation. Methods: A retrospective data analysis was conducted on 20 eyes of 12 patients undergoing bilateral laser-assisted in situ keratomileusis surgery, where intraoperative gas bubble migration was observed. Data from age-matched controls without gas bubble migration were also analyzed. Various preoperative and intraoperative parameters were compared between the groups, including refractive error, keratometry, white-to-white (WTW) distance, angle parameters, anterior chamber depth (ACD), central corneal thickness, flap diameter, pulse energy, suction time, anterior chamber width (ACW), angle opening distance (AOD) 500 and AOD 750, trabecular iris space area (TISA) 500, TISA 750, trabecular iris area (TIA) 500, TIA 750, and anterior chamber width (ACW) using CASIA anterior segment optical coherence tomography (ASOCT), to find the correlation between angle anatomy and migration of gas bubble in AC. Results: The study found no significant differences in median age and spherical error between the groups. However, significant differences were observed in WTW (study: 11.5 ± 0.377 mm, control: 11.78 ± 0.181 mm; P = 0.04), ACD (study: 3.39 ± 0.372 mm, control: 3.86 ± 0.284 mm; P = 0.005), angle (study: 35.22° ±4.28°, control: 41.79° ± 3.95°; P = 0.002), ACW (study: 11.37 ± 0.435 mm, control: 11.83 ± 0.264 mm; P = 0.01), flap diameter (study: 8.82 mm, control: 8.68 mm; P = 0.04), and suction time (study: 62 ± 12.89 sec, control: 85.3 ± 13.35 sec; P = 0.0009). The laser energy parameters were similar between the groups. Conclusion: Smaller WTW, larger flap diameter, lower ACD, and ACW are significant predisposing factors for gas bubble migration into the anterior chamber during FS-LASIK. Preoperative evaluations using Pentacam and CASIA ASOCT can help identify eyes at risk.